2011
DOI: 10.1158/1940-6207.capr-10-0280
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Contribution of Ubiquitous 15-Lipoxygenase-1 Expression Loss in Cancer Cells to Terminal Cell Differentiation Evasion

Abstract: Loss of terminal cell differentiation promotes tumorigenesis. 15-LOX-1 contributes to terminal cell differentiation in normal cells. The mechanistic significance of 15-LOX-1 expression loss in human cancers to terminal cell differentiation suppression is unknown. In a screen of 128 cancer cell lines representing more than 20 types of human cancer, we found that 15-LOX-1 mRNA expression levels were markedly lower than levels in terminally differentiated cells. Relative expression levels of 15-LOX-1 (relative to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…Some researches have proved down-regulation of ALOX15 in various human cancers (e.g., cancers of the colon252627, breast28, lung29, and pancreas30, supporting the theory that ALOX15 is a tumor suppressor gene in these cancers. Zou et al found that the ALOX15 promoter was methylated in colorectal cancer cells in vitro and in 36% (18/50) of colorectal cancer patients but virtually absent in the normal colons without history of colorectal cancer or polyps31.…”
Section: Discussionmentioning
confidence: 86%
“…Some researches have proved down-regulation of ALOX15 in various human cancers (e.g., cancers of the colon252627, breast28, lung29, and pancreas30, supporting the theory that ALOX15 is a tumor suppressor gene in these cancers. Zou et al found that the ALOX15 promoter was methylated in colorectal cancer cells in vitro and in 36% (18/50) of colorectal cancer patients but virtually absent in the normal colons without history of colorectal cancer or polyps31.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, other LOXs do not appear to be significantly altered during colonic tumorigenesis [31, 73, 74]. Downregulation of ALOX15 expression has also been reported in various other human cancers, including lung [75], esophageal [76], breast [77], endometrial [78], urinary bladder [79] and pancreatic cancer [80]. Additionally, screening of 128 different human cancer cell lines representing 20 different human cancers, including all common human cancers, showed that ALOX15 expression was markedly repressed [75].…”
Section: Alox15 Inhibits Colorectal Tumorigenesismentioning
confidence: 99%
“…Downregulation of ALOX15 expression has also been reported in various other human cancers, including lung [75], esophageal [76], breast [77], endometrial [78], urinary bladder [79] and pancreatic cancer [80]. Additionally, screening of 128 different human cancer cell lines representing 20 different human cancers, including all common human cancers, showed that ALOX15 expression was markedly repressed [75]. Loss of ALOX15 expression is transcriptionally mediated [81] and independent of substrate availability [31].…”
Section: Alox15 Inhibits Colorectal Tumorigenesismentioning
confidence: 99%
“…Recent research shows that loss of 15-LOX-1 expression is ubiquitous in a very large collection of cancer cell lines (128 cell lines from more than 20 types of human cancer, including all of the more common types-lung, breast, colorectal, prostate, esophageal, gastric, pancreas, liver, head and neck, cervical, ovarian, and endometrial) and 15-LOX-1 downregulation in tumors [12]. When the 15-LOX-1 transgene was re-expressed in colonic epithelial cells of two independent mice, azoxymethane-inducible colonic tumorigenesis was suppressed.…”
Section: -Lox-1 and Colorectal Cancermentioning
confidence: 99%
“…Loss of terminal cell differentiation facilitates tumorigenesis by disrupting the tight cell junction formation required for epithelial-mesenchymal conversion [12]. Studies of reticulocyte maturation into red cells have shown that 15-LOX-1 promotes maturational degradation of organelles [13,14].…”
Section: Introductionmentioning
confidence: 99%